Geothermal energy : utilization, technology and financing - Yadav, Kriti; Sircar, Anirbid; Yadav, Apurwa (Boca Raton ; London : CRC Press, 2022)
'This book focuses on usage of geothermal energy in countries with low enthalpy reservoirs. It initiates with the fundamentals of geothermal energy, classification of geothermal resources and their importance including Enhanced Geothermal Systems (EGS). Further, it discusses creation, production, potential assessment, perspective analysis, life cycle and environment assessments of EGS. It describes applications in the field of geothermal energy with relevant case studies and introduces the application of Machine Learning techniques in the field of geothermal sectors. Features: Focuses on development of low- to moderate geothermal resources; Introduces machine learning tools and artificial intelligence, as applied to geothermal energy; Provides understanding of Geothermal Energy Resources and Enhanced Geothermal Systems; Discusses possibility of Enhanced Geothermal System using spallation and laser drilling; Includes stimulation methods (thermal, hydraulic, chemical, and explosive) and case studies. This book aims at researchers and graduate students in Geology, Clean Energy, Geothermal Energy and Thermal Engineering'--
Introduction to Geothermal Energy Resources -- Enhanced Geothermal System -- Direct Applications: Application of Geothermal water for Sericulture, Aquaculture and Honey Processing -- Indirect Applications: Application of Geothermal water for Milk Pasteurization, Cloth & Food Drying, Desalination and Space Heating and Cooling -- Machine Learning Techniques for Geothermal Energy Sector -- Financing in Geothermal Energy Sector -- Impact of Geothermal Energy on Climate Change and Tackling it with Machine Learning.
OCLC-licensed vendor bibliographic record.
Keywords: Geothermal resources; Geothermal engineering